Abstract proceedings of the 4th Intercontinental Landfill Research Symposium : 4th Intercontinental Landfill Research Symposium, June14th to 16th 2006, Gällivare, Sweden - Lagerkvist, Anders (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2006)
Godkänd; 2006; 20070103 (ysko)